Cunggrang Inscription Site in Pasuruan Regency as a History Learning Source - Maulana, Wildhan Ichzha; Wijayanti, Finna; Fathurrahman, Fathurrahman; Fitriana, Imelda; Khairunnisa, Khairunnisa (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2024)
The purpose of this research is to analyze the potential and suitability of the Cunggrang Inscription as a history learning resource for high school students. This research uses the historical method which 4 stages, heuristics, verification, interpretation, and historiography based on a philological approach. The results showed that the Cunggrang Inscription has relevance to the basic competencies and indicators of class X senior high school history subjects that focus on social, cultural, religious, and government aspects during the Medang Kingdom period of East Java. The information contained in the Cunggrang Inscription helps students know several aspects of learning material on the history of the Medang Kingdom civilization (1) the division of government administrative areas; (2) the formation of special autonomous regions; (3) the structure of government bureaucracy; (4) the ancient Javanese dating system; and (5) Mount Penanggungan as an ancient Hindu spiritual landscape. Through the use of the potential of the Cunggrang Inscription, it can support teachers to create contextual and interesting history learning, so students’ understanding of the history of Hindu civilization, especially during the Medang Kingdom, becomes more comprehensive.